Zirconium tetrachloride revisited. Issue 3 (21st February 2018) - Borjas Nevarez, Rosendo; Balasekaran, Samundeeswari Mariappan; Kim, Eunja; Weck, Philippe; Poineau, Frederic
Abstract : ZrCl4 has been prepared from the reaction of Zr metal and Cl2 gas in a sealed tube and its structure determined at 100, 150, 200, 250, and 300 K. The chain motif is similar to that observed previously in ZrCl4, but the structural parameters and space group differ. Abstract : Zirconium tetrachloride, ZrCl4, is a strategic material with wide‐ranging applications. Until now, only one crystallographic study on ZrCl4 has been reported [Krebs (1970). Z. Anorg. Allg. Chem. 378, 263–272] and that was more than 40 years ago. The compound used for the previous determination was prepared from ZrO2 and Cl2 –CCl4, and single‐crystal X‐ray diffraction (SCXRD) studies on ZrCl4 obtained from Zr metal have not yet been reported. In this context, we prepared ZrCl4 from the reaction of Zr metal and Cl2 gas in a sealed tube and investigated its structure at 100, 150, 200, 250, and 300 K. At 300 K, the SCXRD analysis indicates that ZrCl4 crystallizes in the orthorhombic space group Pca 21 [ a = 6.262 (9), b = 7.402 (11), c = 12.039 (17) Å, and V = 558.0 (14) Å 3 ] and consists of infinite zigzag chains of edge‐sharing ZrCl6 octahedra. This chain motif is similar to that observed previously in ZrCl4, but the structural parameters and space group differ. In the temperature range 100–300 K, no phase transformation was identified, while elongation of intra‐chain Zr…Zr [3.950 (1) Å at 100 K and 3.968 (5) Å at 300 K] and inter‐chain Cl…Cl [3.630 (3) Å at 100 K and 3.687 (9) Å at 300 K] distances occurred.